Kualitas SDM, Persepsi Pelaku UMKM, Pemahaman UMKM, Sosialisasi SAK EMKM Terhadap Implementasi SAK EMKM - Rismawandi Rismawandi; Indah Rahayu Lestari; Rinny Meidiyustiani (Owner : Riset dan Jurnal Akuntansi, 2022)
The purpose of this study was to assess the effect of implementing SAK EMKM for SMEs through four indicators of reflection, namely the quality of human resources as measured by five indicators. Small business perception is measured by seven reflex indicators. MSME understanding is measured by five specific indicators. Socialization of SAK EMKM is measured using five reflection indicators. This type of research is a descriptive quantitative research. The population in this study was 11,746 MSMEs in the food and beverage sector in the city of Tangerang. The survey sample was 100 respondents from MSME actors, obtained using practical or random sampling methods. The data analysis used, with SmartPLS software version 3.2.1, is based on a model that you can think of as an outer model, and an inner model, with hypothesis testing. This study found that the quality of human resources affected the implementation of SAK EMKM, the perception of SAK EMKM actors did not affect the implementation of SAK EMKM, the understanding of SMEs affected the implementation of SAK EMKM, and SAK EMKM socialization did not affect SAK EMKM.